Characterization of clinical-epidemiological factors and neurological comorbidities in people with Epilepsy: A cross-sectional study in Northeastern Brazil (Research, Society and Development, 2024)
Introduction: Epilepsy is a chronic neurological disease that presents with neuropsychiatric comorbidities, further aggravating the morbidity and mortality of people with epilepsy. Objective: To characterize the clinical epidemiological profile of patients with epilepsy, correlating with associated comorbidities. Methodology: Analytical cross-sectional study. Results: 220 medical records were analyzed. The average age at the first seizure was 6.6 years, with a predominance of focal epilepsy (temporal lobe). Focal changes in the neuroimaging examination occurred in 42.2%, as did focal changes in the electroencephalogram examination in 48.5%. As for comorbidities, 20.8% of the studied population has some type of sleep disorder. Intellectual deficit occurred in 53.5% (24.9%, moderate level).  Headaches in 30.6%. Behavior changes present in 20.8% and Autism Spectrum Disorder in 4.1%. There were statistical relevances between temporal lobe epilepsy and sleep disorder, headache and parietal epilepsy, pharmacological polytherapy with worse seizure control and DI. Conclusion: The diagnosis of temporal lobe epilepsy was the most prevalent. As for etiologies, there was a relationship with a congruent explanation, focal epilepsy with structural etiology, generalized epilepsy with genetic etiology, and unknown epilepsy with unknown etiology.  Focal epilepsies were correlated with electroencephalograms with focal changes, as well as neuroimaging. The high prevalence of neuropsychiatric comorbidities with a bidirectional relationship and shared risk factors with the underlying disease, contrasting with the old view that these comorbidities were due to the effect of epileptic seizures.